Cabot reports revenue growth in 4Q and fiscal year 2014. Issue 2 (February 2015) - Unknown
Abstract : Boston-based Cabot Corp reported year-on-year increases in net sales for both its fourth quarter and full fiscal year (FY) ended 30 September 2014. In 4Q 2014, the company achieved net sales of US911 million, up 1.7% compared with net sales of 896 million the previous year. For FY 2014, net sales rose 5.5% to 3.65 billion compared with 3.45 billion a year earlier.